Optimal design of a high-temperature ultrasonic vibration device - Nguyen, Lanphuong; Hung, Chinghua (Sound & Vibration, 2026)
Ultrasonic vibration-assisted manufacturing has emerged as a transformative method for machining hard-to-machine advanced materials. However, implementing these systems in precision high-temperature manufacturing processes like hot glass embossing introduces significant technical challenges due to severe thermal frequency drift and a degradation in output displacement uniformity. This study addresses these issues by presenting a comprehensive multi-physics numerical optimization framework for a 35 kHz high-temperature ultrasonic vibration device. Utilizing a coupled-field Finite Element Analysis (FEA) methodology in ANSYS, the steady-state thermal profile and its corresponding thermo-structural impact on the system’s resonant frequencies and vibration characteristics were accurately modeled and verified. Shape optimization was executed through an automated coupling loop between the FEA workspace and the advanced numerical optimization platform, SmartDO. The results demonstrate that the optimization scheme successfully established a refined horn geometry that accommodates thermal degradation effects. Experimental validation conducted at an operating temperature of 500 °C confirmed that the optimized design maintained structural deviations within a narrow, manageable resonance window (84–99 Hz) while significantly improving output surface displacement distribution. The finalized device achieved an exceptional experimental amplitude uniformity of 8.20%, which matches the numerical simulation trend closely.